2015
DOI: 10.1186/s13099-015-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering chicken gut microbial dynamics based on high-throughput 16S rRNA metagenomics analyses

Abstract: BackgroundChicken gut microbiota has paramount roles in host performance, health and immunity. Understanding the topological difference in gut microbial community composition is crucial to provide knowledge on the functions of each members of microbiota to the physiological maintenance of the host. The gut microbiota profiling of the chicken was commonly performed previously using culture-dependent and early culture-independent methods which had limited coverage and accuracy. Advances in technology based on ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

54
158
3
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(226 citation statements)
references
References 55 publications
54
158
3
11
Order By: Relevance
“…This is in agreement with the low cecal counts of C. perfringens (see Table S1 in the supplemental material). The genus Bacteroides was not detected in the ileum or cecum at any time point, in contrast to reports by other authors of abundances of 1 to 20% in the ileum (55,63) and 18 to 22% in the cecum (55,(63)(64)(65). In the present study, the genus Alistipes, belonging to the same phylum (Bacteroidetes), was found to have an abundance similar to the reported Bacteroides abundances (up to 36%) in the cecum.…”
Section: Discussioncontrasting
confidence: 88%
“…This is in agreement with the low cecal counts of C. perfringens (see Table S1 in the supplemental material). The genus Bacteroides was not detected in the ileum or cecum at any time point, in contrast to reports by other authors of abundances of 1 to 20% in the ileum (55,63) and 18 to 22% in the cecum (55,(63)(64)(65). In the present study, the genus Alistipes, belonging to the same phylum (Bacteroidetes), was found to have an abundance similar to the reported Bacteroides abundances (up to 36%) in the cecum.…”
Section: Discussioncontrasting
confidence: 88%
“…Bacteroides spp., are common bacteria in the intestine, involved in many important metabolic activities, including polysaccharide degradation, carbohydrate fermentation, and prevention of pathogen colonization 54,55 . Bacteroides spp., along with Alistipes spp., of the family Rikenellaceae are some of the main short chain fatty acid producers in the intestine 56 . An increase in short chain fatty acid production could be beneficial for gut health 57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…There are very few reports on microbiological diversity of different food samples studied by HT-NGS. Moreover, the available reports on metagenomics have identified limited microbial diversity in alfalfa sprouts, chicken caeca, gut 30,43,44 without much emphasis on pathogenic nature. V3 region was targeted and the total microbial diversity characterized up to species level.…”
Section: Discussionmentioning
confidence: 99%
“…V3 region was targeted and the total microbial diversity characterized up to species level. Presence of Firmicutes in chicken could be due to cross-contamination with other parts of chicken during meat processing as high incidence of Firmicutes in chicken gut, ilea and caeca have been reported 31,44 . Phylum composition of mung is similar to other metagenomic studies of fresh fruits and vegetable 45 .…”
Section: Discussionmentioning
confidence: 99%